EVALUASI PROGRAM MANAJEMEN KARIER UNTUK GURU PEMULA: DAMPAK PADA KOMPETENSI DAN PROMOSI JABATAN - An Nisa Firdaus; Idha Dewi Wahyu Sofiani; Kuni Fatonah (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2026)
This study aims to evaluate the implementation of a career management program for novice teachers and its impact on the improvement of their competencies and career advancement. The study employs a descriptive qualitative approach, using data collection techniques such as observation, interviews, and documentation. The research subjects consisted of school principals, novice teachers, and program coordinators. The results showed that the career management program, implemented through orientation, induction, and clinical supervision, had a positive impact on the improvement of novice teachers’ pedagogical, professional, personal, and social competencies, and supported their readiness for promotion through the development of portfolio documentation. Factors supporting the program include school principal leadership and the existence of a professional learning community, while inhibiting factors include administrative burdens, training that is not fully aligned with needs, and limitations in digital infrastructure. This study concludes that the career management program has made a positive contribution but still requires improvements in the areas of supervision documentation, reduction of administrative burdens, needs-based training design, and strengthening of digital infrastructure.